Flexible Photovoltaic Devices: High‐Performance Flexible Nanostructured Silicon Solar Modules with Plasmonically Engineered Upconversion Medium (Adv. Energy Mater. 21/2015). Issue 21 (November 2015) - Lee, Sung‐Min; Li, Weigu; Dhar, Purnim; Malyk, Sergey; Wang, Yu; Lee, Wonmok; Benderskii, Alexander; Yoon, Jongseung
Abstract : In article number 1500761, Jongseung Yoon and co‐workers report a photovoltaic system that can improve the collection efficiency of above‐bandgap, long‐wavelength photons in ultrathin nanostructured silicon solar cells. A flexible composite solar module integrated with silver nanostructures and upconversion printing medium enables the enhanced photovoltaic performance of surface‐embedded 8‐μm‐thick silicon microcells via synergistic contributions from plasmonically amplified spectral upconversion, waveguiding, and fluorescence of the upconversion medium.